Anatomy, Functionality, and Neuronal Connectivity with Manganese Radiotracers for Positron Emission Tomography. - Saar, Galit; Millo, Corina M.; Szajek, Lawrence P.; Bacon, Jeff; Herscovitch, Peter; Koretsky, Alan P. (Molecular Imaging & Biology, 2018)
Purpose: Manganese ion has been extensively used as a magnetic resonance imaging (MRI) contrast agent in preclinical studies to assess tissue anatomy, function, and neuronal connectivity. Unfortunately, its use in human studies has been limited by cellular toxicity and the need to use a very low dose. The much higher sensitivity of positron emission tomography (PET) over MRI enables the use of lower concentrations of manganese, potentially expanding the methodology to humans.Procedures: PET tracers manganese-51 (Mn-51, t1/2 = 46 min) and manganese-52 (Mn-52, t1/2 = 5.6 days) were used in this study. The biodistribution of manganese in animals in the brain and other tissues was studied as well as the uptake in the pancreas after glucose stimulation as a functional assay. Finally, neuronal connectivity in the olfactory pathway following nasal administration of the divalent radioactive Mn-52 ([52Mn]Mn2+) was imaged.Results: PET imaging with the divalent radioactive Mn-51 ([51Mn]Mn2+) and [52Mn]Mn2+ in both rodents and monkeys demonstrates that the accumulation of activity in different organs is similar to that observed in rodent MRI studies following systemic administration. Furthermore, we demonstrated the ability of manganese to enter excitable cells. We followed activity-induced [51Mn]Mn2+ accumulation in the pancreas after glucose stimulation and showed that [52Mn]Mn2+ can be used to trace neuronal connections analogous to manganese-enhanced MRI neuronal tracing studies.Conclusions: The results were consistent with manganese-enhanced MRI studies, despite the much lower manganese concentration used for PET (100 mM Mn2+ for MRI compared to ~ 0.05 mM for PET). This indicates that uptake and transport mechanisms are comparable even at low PET doses. This helps establish the use of manganese-based radiotracers in both preclinical and clinical studies to assess anatomy, function, and connectivity.